Elasmobranch genome sequencing reveals evolutionary trends of vertebrate karyotype organization - Yamaguchi, Kazuaki; Uno, Yoshinobu; Kadota, Mitsutaka; Nishimura, Osamu; Nozu, Ryo; Murakumo, Kiyomi; Matsumoto, Rui; Sato, Keiichi; Kuraku, Shigehiro (Genome Research, 2023)
Genomic studies of vertebrate chromosome evolution have long been hindered by the scarcity of chromosome-scale DNA sequences of some key taxa. One of those limiting taxa has been the elasmobranchs (sharks and rays), which harbor species often with numerous chromosomes and enlarged genomes. Here, we report the chromosome-scale genome assembly for the zebra shark Stegostoma tigrinum, an endangered species that has a relatively small genome among sharks (3.71 Gb), as well as for the whale shark Rhincodon typus. Our analysis using a male–female comparison identified an X Chromosome, the first genomically characterized shark sex chromosome. The X Chromosome harbors the Hox C cluster whose intact linkage has not been shown for an elasmobranch fish. The sequenced shark genomes show a gradualism of chromosome length with remarkable length-dependent characteristics—shorter chromosomes tend to have higher GC content, gene density, synonymous substitution rate, and simple tandem repeat content as well as smaller gene length and lower interspersed repeat content. We challenge the traditional binary classification of karyotypes as with and without so-called microchromosomes. Even without microchromosomes, the length-dependent characteristics persist widely in nonmammalian vertebrates. Our investigation of elasmobranch karyotypes underpins their unique characteristics and provides clues for understanding how vertebrate karyotypes accommodate intragenomic heterogeneity to realize a complex readout. It also paves the way to dissecting more genomes with variable sizes to be sequenced at high quality.